KARAKTERISASI GEOTEKNIK BERDASARKAN DATA KECEPATAN GELOMBANG GESER (Vs) DENGAN METODE ANALISIS MULTIKANAL GELOMBANG PERMUKAAN DI DAERAH GABUS, GROBOGAN, JAWA TENGAH - , ROMA WIDIYANSARI; , Eddy Hartantyo, S.Si., M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Multichannel Analysis of Surface Wave survey has been conducted to investigate geotechnical properties in 3 location. They are location 1 in Ledok Formation, location 2 in Lidah Formation and location 3 in Lidah Formation. The acquisition use 5 kg of sledgehammer as seismic source with iron plate as an anvil. Twenty four channel of geophones is used as receivers and digital seismic data logger as recorder. Collected data is analyzed by SeisImager/SW software. Geometrical correction is applied to shot gather data based on configuration in field data acquisition. To convert data in time-offset domain to frequency-wavenumber domain we used f-k transformation. The next step is picking velocity in Rayleigh wave fundamental mode to get dispersion curve. This dispersion curve is inverted to get 1-D ôô¯¦ profile as function of depth. Based on this survey, seismic site characteristic of each survey location can be evaluated based on ôô¯¦ values. Location 1 with dominant lithology is glauconite sandstone, have result ôô¯¦ values < 180 m/s (soft soil) at depth 0-8 m, 180 < ôô¯¦ < 360 m/s (stiff soil) at depth 8-17 m and 360-658 m/s (very dense soil) at depth 17-30 m. Location 2 with dominant lithology is napal, have result ôô¯¦ values < 180 m/s at depth 0-9 m, 180 < ôô¯¦ < 360 m/s at depth 9-17 m and 360 < ôô¯¦ < 658 m/s at depth 17-30 m. Location 3 in Lidah Formation with dominant lithology is claystone, have result ôô¯¦ values < 180 m/s at depth 0-12 m and 180 < ôô¯¦ < 336 m/s at depth 12-30 m.